Transparent Soap Formulation from Soursop Fruit Juice (Annona muricata L.) as a Skin Moisturizer - Maysarah, Aulya; Yuniarti, Rafita (Pustaka Media Publishing, 2024)
Transparent soap preparation formulation from soursop fruit juice (Annona muricata L.) as a skin moisturizer has been carried out. Soursop fruit juice is known to have a high polyphenol compound content and contains a lot of vitamin C which has antioxidant activity. Transparent soap formulation uses soursop fruit juice with concentrations of 20, 30, and 40. Evaluation of transparent soap formulation includes organoleptic tests, water content, foam height, irritation, humidity and preference or hedonic. The results of the moisture test on the blank obtained a difference of 0.66%, while in formula I there was a difference of 4.33%, in formula II there was a difference of 5%, and in formula III there was a difference of 8.66%. The results of the moisture test on the skin showed that the highest humidity was obtained in the formula with a concentration of 40% there was a difference of 8.66%. Transparent soap from soursop fruit juice in the water content test, foam height, and pH test had results that met the requirements according to SNI (Indonesian National Standard). The conclusion of this study is that soursop juice can be formulated into transparent soap and meets SNI requirements.